Cultural events - does attendance improve health? Evidence from a Polish longitudinal study - Dorota Węziak-Białowolska; Piotr Białowolski (BMC, 2016)
Abstract Background Although there is strong advocacy for uptake of both the arts and creative activities as determinants of individual health conditions, studies evaluating causal influence of attendance at cultural events on population health using individual population data on health are scarce. If available, results are often only of an associative nature. In this light, this study investigated causative impact of attendance at cultural events on self-reported and physical health in the Polish population. Methods Four recent waves (2009, 2011, 2013 and 2015) of the biennial longitudinal Polish household panel study, Social Diagnosis, were analysed. The data, representative for the Polish population aged over 16, with respect to age, gender, classes of place of residence and NUTS 2 regions, were collected from self-report questionnaires. Causative influence of cultural attendance on population health was established using longitudinal population representative data. To account for unobserved heterogeneity of individuals and to mitigate issues caused by omitted variables, a panel data model with a fixed effects estimator was applied. The endogeneity problem (those who enjoy good health are more likely to participate in cultural activities more frequently) was circumvented by application of instrumental variables. Results Results confirmed positive association between cultural attendance and self-reported health. However, in contrast to the often suggested positive causative relationship, such a link was not confirmed by the study. Additionally, no evidence was found to corroborate a positive impact from cultural attendance on physical health. Both findings were substantiated by augmentation in the longitudinal perspective and causal link. Conclusions We showed the relation between attendance at cultural events and self-reported health could only be confirmed as associational. Therefore, this study provided little justification to encourage use of passive cultural participation as a measure of health promotion (improvement). Our study did not confirm any identifiable benefit to physical health from passive participation in culture. Future research should investigate the causative influence of active participation in creative activities on health outcomes as, in contrast to passive attendance, it may be influential.